Klasifikasi Penerima Beasiswa Aceh Carong (Aceh Pintar) Di Universitas Malikussaleh Menggunakan Algoritma Knn (K-Nearest Neighbors) - Ar Razi (Jurnal Tika, 2022)
Aceh Carong Scholarship is a program from the Aceh Government to help Acehnese children who want to continue their education by obtaining scholarships from the Aceh Government. Currently, the selection process for Aceh Carong scholarship recipients at Malikussaleh University is carried out using a manual system so that the selection process has not been effective and efficient in its application. K-Nearest Neighbor is a method that can be used to classify new test data based on training data. In this study, the results obtained where the use of the KNN algorithm for the classification of Aceh Carong Scholarship recipients obtained an accuracy of  82.00%.